If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4y) + -9(y) + 1 = 0 Remove parenthesis around (4y) 8 * 4y + -9(y) + 1 = 0 Multiply 8 * 4 32y + -9(y) + 1 = 0 Reorder the terms: 1 + 32y + -9y = 0 Combine like terms: 32y + -9y = 23y 1 + 23y = 0 Solving 1 + 23y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 23y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 23y = 0 + -1 23y = 0 + -1 Combine like terms: 0 + -1 = -1 23y = -1 Divide each side by '23'. y = -0.04347826087 Simplifying y = -0.04347826087
| -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) | | -4n=-9 | | y=ln(x)+c | | Ax(x-1)+B(x+1)(x-1)+C(x+1)x=x^2+4 | | -4b=11 | | 8x+2=4x-24 | | 11-6= | | -34=-2(3x+5) | | 6f+5(4f+3)= | | 6(2n+8)=102 | | 107=107(47-y) | | 4(3n-3)=48 | | 2x^2+25x+20=-x^2-8 | | 2(y-1)=3(y-6) | | 2x(x+3)=2x^2+6x | | 6x+4y+7z-3x+3z-5y= | | cos(3x+30)=0.5 | | =(x-3*x)+(x-3*x)+(x*x+5)+(x*x+5)+(x-3)*(x+5)+(x-3)*(x+5) |